“2015, o ano que não terminou”: experiências e memórias acerca da greve dos trabalhadores da educação e o massacre em 29 de abril - Tadiotto, Rubia Mara (2019)
Look at the strike and realize the importance of workers’ social practices, as wellto analyze how they experienced this processare the main efforts of this work. In the year 2015, education workers in the state pf Paraná lived a long and conflictive strike, with its peak April 29, marked by violence and usurpation of the rights of these workers. In this sense, this dissertation sought to analyze the conflicts lived internally in the category during these confrontations and how they deal with this memory.Understand also, what is the understanding and meaning given to the day that was marked as the massacre of April 29, 2015 by these guys. We are interested, above all, in understanding how these people, after having their life, dynamics altered, leave a striking movement. The special selected cut was to the southwestern region of Paraná, which counts on na active participation of the teachers in the striking movements.